Multidiscip Cancer Investig 2019
DOI: 10.30699/acadpub.mci.3.4.5
|View full text |Cite
|
Sign up to set email alerts
|

The Caring-related Problems Experienced by Family Caregivers of Patients With Breast Cancer: A Descriptive Study

Abstract: Introduction: The diagnosis of cancer involves the patients, their caregivers, and families. Caregivers should obtain guidance from health care professionals to promote care facilities. The current study aimed at investigating the economic, socio-individual, informational, and psycho-spiritual problems of caregivers in post-treatment phase of breast cancer. Methods: The present descriptive study was conducted on 251 subjects using a ques- tionnaire consisted of demographic part and the caregivers’ difficulties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…[15] Studies have shown that family caregivers are not adequately prepared for homebased caregiving and do not receive adequate education about caregiving before their patients are discharged from hospital. [13,16] In addition to a lack of knowledge and limited support, most family caregivers experience an imbalance between their caregiver burden and their own personal needs, which results in many different negative physical, psychological, financial, social, and occupational consequences and negatively affects their quality of life. [8,9,11,14,17] Healthcare providers have an important role in identifying and resolving the challenges faced by family caregivers of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Studies have shown that family caregivers are not adequately prepared for homebased caregiving and do not receive adequate education about caregiving before their patients are discharged from hospital. [13,16] In addition to a lack of knowledge and limited support, most family caregivers experience an imbalance between their caregiver burden and their own personal needs, which results in many different negative physical, psychological, financial, social, and occupational consequences and negatively affects their quality of life. [8,9,11,14,17] Healthcare providers have an important role in identifying and resolving the challenges faced by family caregivers of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study in Iran found that all family caregivers had physical, emotional, financial, and informational problems and 97%, 89%, and 74% of them suffered from psychological, financial, and spiritual problems, respectively. [ 16 ] Another study in Iran showed that family caregivers of cancer patients had unfulfilled needs, mostly in terms of receiving information, attention, and respect from healthcare providers as well as health-related and psychological problems. [ 11 ] A qualitative study in the United Kingdom into patients’ and family caregivers’ experiences of living with a jejunostomy feeding tube after surgery for esophagogastric cancer also showed that they suffered from different physical problems, concerns, and problems in daily living.…”
Section: Introductionmentioning
confidence: 99%